Role of Bariatric Surgery in Chronic Kidney Disease Patients. Issue 4 (October 2016) - Grimaldi, Rosa; Muci, Maria Luisa; Rotondi, Silverio; Tartaglione, Lida; Rizzello, Mario; Abbatini, Francesca; Silecchia, Gianfranco; Mazzaferro, Sandro
Bariatric surgery represents the elective treatment of severe obesity (BMI≥40Kg/m 2 ) since it results in better control of cardiovascular risk factors and comorbidities typically associated with obesity, like diabetes, hypertension and dyslipidemia. Obesity is a recognized independent risk factor for chronic kidney disease and for progression of renal insufficiency. Pathomechanisms are still incompletely known. Obesity is associated with hyper-filtration, microalbuminuria and proteinuria all of which favor renal disease and its progression. This narrative review reports on the available evidence linking bariatric surgery and renal function since this surgery may affect proteinuria, hyper-filtration and glomerular filtration rate. Although available data are limited in particular in cases with more advanced stages of renal failure, bariatric surgery associates with improved filtration and lower proteinuria in patients with mild to moderate renal insufficiency. In patients with more advanced stages of renal failure, surgery should be considered if obesity represents a relative contraindication to transplantation. Surgery seems to improve graft survival. Further, nephrologists should be informed on the metabolic and nutritional changes associated with bariatric surgery, which could be responsible for untoward effects requiring early identification and treatment. Bariatric surgery could be a valid therapeutic option in renal patients to improve the negative clinical outcomes of obese subjects.